Optimization of Vat Dyeing with an Orange Peel Extract Reducing Agent using Response Surface Methodology. Issue 1 (January 2020) - Islam, Mohammad Tajul; Mazumder, Nur-Us-Shafa; Asaduzzaman, Syed
Sodium dithionite is the most commonly-used reducing agent for vat dyeing of cotton fabric. This research focuses on the use of orange peel extract (OPE) as a new reducing agent for vat dyeing cotton fabric to avoid the toxic chemicals released from sodium dithionite. The dyeing experiments were carried out in a batch system to optimize alkali concentration, OPE concentration, and vatting temperature via response surface methodology (RSM). The optimal color yield was achieved at 11.97 g/L of OPE, 1.18 g/L of alkali, and 44 °C vatting temperature. Fabric dyed under optimized dyeing condition using OPE was compared with a standard conventionally dyed fabric using sodium dithionite as the reducing agent. A uniformly dyed fabric with comparable color yield was obtained. Fastness properties were not affected by the use of OPE.